CERTAIN CLASSES OF ANALYTIC FUNCTIONS ASSOCIATED WITH SAIGO’Sq-NTEGRAL OPERATOR - M.M.GOUR, G.S.SHARMA, PINKYLATA, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The q-analysis theory has recently been utilized in numerous disciplines of science and engineering. In q-theory, the fractional q-calculus is an extension of the regular fractional calculus. A great work with q-calculus and fractional q-calculus operators has been investigated by Srivastava [4].In a previous paper Purohit and Raina [8], Investigated applications of fractional q-calculus operators to defined certain new classes of functions which are analytic in the open disk U={ξ∈C||ξ|<1}.Several others have previously released new classes of analytical functions with the help ofq-calculus operators. Purohit [7], Purohit and Raina [9]-[11] gived related work and added various classes of univalent and multi valently analytic functions in open unit disk U. For any more inquiries on the analytic classes, we refer to [1], [5]-[6] and [12][16]for functions described by applying q-calculus operators and subject related to the this work. In the current inquiry, we are planning to develop few new classes of analytic functions applying the Saigo integral operator in q calculus. The results obtained must also provide the coefficient in equalities. First we use the main notations and definitions intheq-calculus which are relevant to grasp the object of the study.